Exploring the Potential of Carbon-based Radar Absorbing Material Innovations - Fahri, Mirad; Bolilanga, Patricya Inggrid Wilhelmina; Gunaryo, Gunaryo; Stiawan, Elva; Kurniadi, Tedi (Indonesian Journal of Chemical Studies, 2024)
This review explored the potential of carbon-based radar-absorbing materials (RAM), which had gained significant attention due to their superior properties and performance. In response to the growing demand for stealth technology in the military and civilian sectors, traditional radar-absorbing materials encountered limitations: weight, cost, and effectiveness. Carbon-based materials, such as carbon nanotubes, graphene, and various composites, offered lightweight, flexible, and tunable solutions that enhanced electromagnetic wave absorption across a wide frequency range. This paper examined the underlying mechanisms of radar wave absorption in carbon-based materials, highlighting their advantages over conventional options. In addition, recent advancements in fabrication techniques, including 3D printing and hybrid composite development, were also discussed, emphasizing their role in optimizing performance and sustainability. By synthesizing current research findings, this review aimed to provide a comprehensive understanding of the carbon-based RAM potential in advancing the future of stealth technology. Ultimately, this study presented insights that contribute to the continuing investigation in advanced materials science, suggesting a potential way to develop materials that can enhance radar absorption capabilities and extend their applications in modern technology.